2018
DOI: 10.3198/jpr2017.09.0068crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of High Alpha‐Acid Male Hop Germplasm USDA 21267M

Abstract: USDA 21267M (Reg. No. GP-37, PI 559093) male hop (Humulus lupulus L. var. lupulus) germplasm was released to the public 6 Dec. 2011. This germplasm has been used by the USDA-ARS for hop cultivar development for several decades. Nonagency interest in this germplasm was expressed, and release of this material is considered beneicial for the US public. USDA 21267M arose from a cross, made in 1973 involving the hop cultivar Comet and the USDA-ARS hop male germplasm 21110M. The deining characteristics of USDA 21267… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In general, this study has cautiously shown that small effect and pleiotropic loci underscore the genetic architecture of DMR in hop in 64035M, a line that has played an important role in cultivar development in hop (e.g., Henning & Haunold, 1999a, 1999b, 2012; Henning et al., 2018, 2021). There are two major caveats associated with our study.…”
Section: Resultsmentioning
confidence: 78%
“…In general, this study has cautiously shown that small effect and pleiotropic loci underscore the genetic architecture of DMR in hop in 64035M, a line that has played an important role in cultivar development in hop (e.g., Henning & Haunold, 1999a, 1999b, 2012; Henning et al., 2018, 2021). There are two major caveats associated with our study.…”
Section: Resultsmentioning
confidence: 78%